Effect of magnetized water irrigation on Cd subcellular allocation and chemical forms in leaves of Festuca arundinacea during phytoremediation - Jie Luo; Siyao Feng; Mingpo Li; Yue He; Yuping Deng; Min Cao (Ecotoxicology and Environmental Safety, 2024)
The application of an external magnetic field has been shown to improve the Cd phytoremediation efficiency of F. arundinacea by leaf harvesting. However, the influencing mechanisms of the promoting effect have not yet been revealed. This study evaluated variations in the Cd subcellular allocation and fractions in various F. arundinacea leaves, with or without magnetized water irrigation. Over 50 % of the metal were sequestered within the cell wall in all tissues under all treatments, indicating that cell wall binding was a critical detoxification pathway for Cd. After magnetized water treatment, the metal stored in the cytoplasm of roots raised from 33.1 % to 45.3 %, and the quantity of soluble Cd in plant roots enhanced from 53.4 % to 59.0 %. The findings suggested that magnetized water mobilized Cd in the roots, and thus drove it into the leaves. In addition, the proportion of Cd in the organelles, and the concentration of ethanol-extracted Cd in emerging leaves, decreased by 13.0 % and 47.1 %, respectively, after magnetized water treatment. These results explained why an external field improved the phytoextraction effect of the plant through leaf harvesting.